Penerapan Kompetensi dan Motivasi Mengajar untuk Meningkatkan Kinerja Pendidik PAI di Sekolah Dasar Kecamatan Leuwiliang Kabupaten Bogor - Muhamad Yusuf Ibrahim; Ami Primarni; Riyanto (Jurnal Dirosah Islamiyah, 2024)
This study aims to assess the implementation of competence and motivation in efforts to improve the performance of Islamic Education (PAI) teachers in elementary schools located in Leuwiliang District, Bogor Regency. The focus of the research is on three main elements: competence, motivation, and teacher performance. Competence encompasses the knowledge, skills, and attitudes required for teachers to carry out their duties professionally. Motivation is understood as the internal drive that influences teachers' behavior in their work, while teacher performance is evaluated based on their ability to manage learning, mastery of subject matter, and student assessment. Using a qualitative approach, this study reveals that the optimal application of competence and motivation positively impacts teacher performance, particularly in lesson planning and delivery. Factors such as the availability of facilities and challenges in technology comprehension also affect performance. The study recommends ongoing development programs to enhance pedagogical competence and technological skills among PAI teachers.